Is there is an association between the presence of Staphylococcus species and occurrence of vernal keratoconjunctivitis? - Al-Hakami, Ahmed M. (Saudi J Ophthalmol, 2015)
PURPOSE: The aim of this study was to identify the association of normal bacterial flora with vernal keratoconjunctivitis (VKC) occurrence in VKC and non-VKC groups. METHODS: Conjunctival specimens were collected from 18 VKC patients and 22 healthy controls, cultured and identified following standard methods. The association between the presence of bacteria and occurrence of VKC was analyzed using Chi square statistic. RESULTS: Comparable bacterial growth was observed in VKC (77.8%) as well as control group (77.2%) (p = 0.970). Analysis of individual bacterial revealed that Staphylococcus aureus was detected more frequently in VKC (27.78% vs. 4.55% in control, p = 0.041) and Staphylococcus epidermidis was found much more commonly in the control eyes (45.45% in control vs. 5.56% in VKC, p = 0.005). CONCLUSIONS: An aggravating role of S. aureus colonization in the occurrence of VKC, and a possible role of S. epidermidis against the occurrence of VKC were concluded.